PEMBELAJARAN PENJASORKES MELALUI MEDIA BERMAIN BOLA KERANJANG TERHADAP HASIL BELAJAR SISWA SDLB-C TUNA GRAHITA (Department of Physical Education, Sport, Health and Recreation, 2014)
The problem in this study is whether there is an increase in Penjasorkes learningoutcomes through media play basket ball for mentally students disabled SDLB-CEducation Foundation Exceptional Demak?. This study aims to improve learn-ingoutcomes through the Penjasorkes media play basket ball for students learningSDLB-C in Physical Education, Sport and Health. This study uses classroomaction research. In the implementation of the first cycle and second cycle ofmeetings held 1 meeting, where each cycle has shown an increase Penjasorkeslearning outcomes and meet the completeness criteria are minimal so it does notneed to be held next cycle. Based on the results, the results of the percentage ofcompletion on the first cycle that can meet the KKM is equal to 52.94% of thetotal number of students in the second cycle and increased to 88.23% of the totalnumber of students. Based on the above results, it can be concluded that thePenjasorkes learning using media play basket ball can improve the process inimproving learning outcomes for mentally disabled students SDLB-C EducationFoundation Exceptional Demak. Expected for Penjasorkes teachers in SDLB-Ccan use the media playing basket ball in the learning of Physical Education, Sportand Health, as an alternative to implement-ing the learning.